Development and Maintenance of a Biospecimen Repository for Clinical Samples Derived from Pulmonary Patients. Issue 4 (29th May 2014) - Schwiebert, Lisa M.; Estell, Kim; Meadows, Tonja; Thannickal, Victor J.; Rowe, Steven; Sorscher, Eric J.; Harris, W. Thomas; Gaggar, Amit; Dransfield, Mark; de Andrade, Joao A.
Abstract The Pulmonary Biospecimen Repository (PBR) at the University of Alabama at Birmingham (UAB) was launched in 2009. The purpose of the UAB PBR is to provide investigators within the pulmonary community at UAB and elsewhere with clinical samples derived from multiple lung diseases, including transplant recipients, idiopathic pulmonary fibrosis, chronic obstructive pulmonary disease, cystic fibrosis, and asthma. Cell and fluid samples isolated from bronchoalveolar lavage (BAL), plasma, and serum are collected and stored; samples are assessed routinely for viability. Each sample is linked directly with the respective patient information via the Pulmonary Translational Research and Clinical Database, a Health Insurance Portability and Accountability Act compliant database that includes detailed information allowing for the study of specific patient cohorts. To access samples, investigators must complete a request form, which is reviewed by the UAB PBR Steering Committee. To date, more than 800 patients have provided approximately 7, 000 BAL, serum and plasma fluid, and cell samples. Over the past 4 years, nearly 800 of these samples have been distributed to investigators at UAB and elsewhere. Future plans for the UAB PBR include expanding sample collection to additional pulmonary diseases, such as mycobacterial infections, increasing the number of sample users and obtaining external funding to ensure its continued sustainability.